QSAR studies of indoyl aryl sulfides and sulfones as reverse transcriptase inhibitors - Duchowicz, Pablo Román (2018)
The inhibitory HIV reverse transcriptase activity of 172 non-nucleoside indoyl aryl sulfones and sulfides is studied with a QSAR analysis, in order to identify the molecular characteristics influencing the interaction with the reverse transcriptase enzyme. This work increases the available QSAR studies of indoyl aryl sulfones and sulfides using the reported experimental EC₅₀ values against HIV-1 wild type (IIIB) in human T-lymphocyte (CEM) cells. Different approaches are proposed, involving 0D, 1D and 2D molecular descriptors from PaDEL freeware, and also based on flexible descriptors from CORAL freeware. Three models are finally presented, which correlate the inhibitory HIV reverse transcriptase activity with good accuracy. It is demonstrated that the established models are predictive in the validation process. The novelty of the present work relies on the development of structure-inhibitory HIV activity relationships, through a computational technique that does not require the knowledge of the molecular conformation during the structural representation. The obtained results would contribute to guide the design of more effective compounds for HIV treatment.